2014
DOI: 10.1016/j.bbamem.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The periplasmic domain of Escherichia coli outer membrane protein A can undergo a localized temperature dependent structural transition

Abstract: Gram-negative bacteria such as Escherichia coli are surrounded by two membranes with a thin peptidoglycan (PG)-layer located in between them in the periplasmic space. The outer membrane protein A (OmpA) is a 325-residue protein and it is the major protein component of the outer membrane of E. coli. Previous structure determinations have focused on the N-terminal fragment (residues 1-171) of OmpA, which forms an eight stranded transmembrane β-barrel in the outer membrane. Consequently it was suggested that OmpA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 75 publications
0
44
1
Order By: Relevance
“…in OmpA from certain bacteria, which comprises the least stable region of the protein as shown by a NMR study (24) and previous computational simulations (29). The lysine and arginine residues are conserved in homologs from Salmonella enterica and Neisseria meningitides and, based on their crystal structures, are positioned similarly compared to the ones in E. coli (Fig.…”
Section: The Ompa Dimer Readily Binds To Pgnmentioning
confidence: 74%
See 1 more Smart Citation
“…in OmpA from certain bacteria, which comprises the least stable region of the protein as shown by a NMR study (24) and previous computational simulations (29). The lysine and arginine residues are conserved in homologs from Salmonella enterica and Neisseria meningitides and, based on their crystal structures, are positioned similarly compared to the ones in E. coli (Fig.…”
Section: The Ompa Dimer Readily Binds To Pgnmentioning
confidence: 74%
“…The E. coli outer membrane porin OmpA is a multidomain protein whose N-terminal domain (NTD) is made of a b-barrel and C-terminal domain (CTD) is a globular periplasmic unit that binds to PGN, connected by an unstructured 20-residue linker region (18). The NTD has been subject to numerous functional and structural studies (19)(20)(21)(22)(23), whereas the structure of the CTD has recently emerged from a NMR study (24). Experimental evidence suggests that the full-length OmpA can form a homodimer (25,26), the model of which has been proposed and validated by mass spectrometry and MD simulations (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…S4c). The predicted structure of the OprF C-terminal domain was superimposed onto the corresponding region of OmpA crystal structure (PDB identifier: 2MQE) (Ishida et al, 2014) to identify regions of variability and the two proteins showed high structural similarity, also reflected in the high TM-score of the predicted model. Importantly, the region of OmpA dimerization interface and the corresponding superimposed region of OprF monomer containing cross-link sites showed identical secondary structures.…”
Section: Discussionmentioning
confidence: 99%
“…2 D). The N- and the C- terminal domains of OmpA are connected by a short region (residues 173–190) with unresolved structure that forms a flexible linker [28] . Basing on our tridimensional model, a set of twelve ompA fragments were PCR-generated ( Fig.…”
Section: Discussionmentioning
confidence: 99%